Buying Intention Determinants of Muslim Consumer Behaviour in Purchasing Halal Products Mediated by Buying Intention - Andika Akbar,; Mukhtar Lutfi,; Abdul Wahab, (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
This research is a study of the determination of Muslim consumer behaviour in purchasing halal products through the development of TPB by developing halal literacy variables. The type of research used in this research is quantitative research. The location of this research was at Muhammadiyah Bone University with 120 student samples. The results of this study indicate that halal literacy and attitudes have a significant influence on the purchasing behaviour of Muhammadiyah Bone University students in buying halal products. Halal literacy, as measured by understanding and knowledge of halal concepts, as well as positive attitudes towards halal products, strongly influence purchasing decisions. In contrast, subjective norms and perceived behavioural control did not show a significant influence on purchasing behaviour. Buying intention also has a significant effect on purchasing behaviour and acts as a strong predictor of actual behaviour. However, buying intention does not significantly mediate the relationship between halal literacy and purchasing behaviour, as well as between subjective norms and perceived behavioural control and purchasing behaviour. The mediation of buying intention between attitude and purchase behaviour was close to significance, but not strong enough to be considered significant.